MANAJEMEN STRATEGIK MUTU PENDIDIKAN - Baharuddin, Baharuddin (Idaarah: Jurnal Manajemen Pendidikan, 2019)
School management with a strategic design is considered as successful if it is able to raise the quality of the processes and products of quality education and learning. Therefore the ability of the principal, school personnel and others who can implement a strategy in a school is very important, in relation to the ability of the principal as a leader and teacher as a professional who is responsible for the progress of students. The principal is required to have the ability to manage and formulate the development of the vision, mission and goals of the school and identify school programs that can support the learning process which includes curriculum, human resources, facilities and infrastructure, providing guidance for educators, and dynamic active participation from parents, including institutions / institutions that have concern for education.